2011
DOI: 10.1111/j.1600-6143.2011.03593.x
|View full text |Cite
|
Sign up to set email alerts
|

High Mean Fluorescence Intensity Donor-Specific Anti-HLA Antibodies Associated With Chronic Rejection Postliver Transplant

Abstract: In contrast to kidney transplantation where donorspecific anti-HLA antibodies (DSA) negatively impact graft survival, correlation of DSA with clinical outcomes in patients after orthotopic liver transplantation (OLT) has not been clearly established. We hypothesized that DSA are present in patients who develop chronic rejection after OLT. Prospectively collected serial serum samples on 39 primary OLT patients with biopsy-proven chronic rejection and 39 comparator patients were blinded and analyzed for DSA usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
140
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(149 citation statements)
references
References 17 publications
8
140
0
1
Order By: Relevance
“…The prevalence of preformed DSAs and de novo DSAs was, respectively, 60% and 62% in the chronic rejection group, and 41% (p ¼ ns) and 38% (p ¼ 0.047) in patients with no rejection (18). The proportion of patients who had an MFI !10 000 was also significantly greater in patients with chronic rejection (52% vs. 13%, p < 0.0001) (18). Surprisingly, in this latter study, 61% of patients who had DSAs did not present with any rejection episodes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of preformed DSAs and de novo DSAs was, respectively, 60% and 62% in the chronic rejection group, and 41% (p ¼ ns) and 38% (p ¼ 0.047) in patients with no rejection (18). The proportion of patients who had an MFI !10 000 was also significantly greater in patients with chronic rejection (52% vs. 13%, p < 0.0001) (18). Surprisingly, in this latter study, 61% of patients who had DSAs did not present with any rejection episodes.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-controlled study, O'Leary et al (18) found DSAs in 92% of patients with chronic rejection compared to 61% in those with no history of acute or chronic rejection (p ¼ 0.003). The prevalence of preformed DSAs and de novo DSAs was, respectively, 60% and 62% in the chronic rejection group, and 41% (p ¼ ns) and 38% (p ¼ 0.047) in patients with no rejection (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations